Plan estratégico de marketing para la asociación “ASOCATAYU” de la ciudad de Catamayo, provincia de Loja - Ruiz Valdivieso, Lucila Gardenia (2016)
This research work has the general objective Develop a Strategic Marketing Plan for the city ASOCATAYU Association of Catamayo, Loja province, in order to meet the needs of its customers, thus achieving stability, permanence and profitability. To meet this objective different methods as scientific, deductive, inductive, analytical, descriptive and historical were used and made use of various techniques such as conducting an interview with the administrator and the application of surveys to the 15 employees of the entity and a sample of 288 customers. The information obtained allowed a diagnosis of the current situation of the entity. Externally, the Evaluation Matrix of external factors, the result of higher 2.57 to 2.5 indicates that there is a predominance of opportunities over threats, which must be harnessed to strengthen its growth. Internally, the Evaluation Matrix Internal Factors resulting from 2,58 higher than 2.5 reveals that there is predominance of the strengths of weaknesses, indicating that while there are problems in the Association are not serious or interfere its growth. The four elements of SWOT analysis allowed for the crossing of the variables in order to find the strategic through the FO, DO, FA, DA Analysis objectives,being these:. Facilitating the acquisition of services by purchasing consumer cards pre -payment transferable, with a budget of $ 1,700.00; Designing an advertising plan in the mainstream media to make known the services provided by the Association at a cost of $ 2,881.00; Outline a plan of promotions to encourage the purchase of services provided ASOCATAYU with an outflow of $ 1625.00; Increase sales by making agreements with local companies, with a budget amounting to $ 150.00; and, implementing a policy of volume purchasing on durable and semi-durable inputs to lower costs, with a cost of $ 200.00. The total budget was $ 6,556.00. In conclusion, the research work aims to position the ASOCATAYU association through a promotional and advertising campaign, capture market through agreements with public and private companies, as well as implement a purchasing policy for consumer durables and semi-durables, which will meet the desires and demands of its customers, achieving their loyalty and capture a larger market. Therefore, it is recommended to apply the strategic partnership marketing plan proposed in order to position themselves in the market, increasing the number of customers and improve their profit margin.